Prognostic relevance of HPV infection and p16 overexpression in squamous cell anal cancer - Mai, Sabine; Welzel, Grit; Ottstadt, Martine; Lohr, Frank; Trunk, Marcus; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2015)
Human papillomavirus (HPV) DNA and p16 status have both been reported as prognostic factors in anal cancer, but the prognostic relevance of combined detection and particularly HPV−/p16+ and HPV+/p16− signatures is unknown. We evaluated combined HPV DNA and p16 status as a prognostic factor of treatment response in anal cancer. 106 patients treated with radiochemotherapy (RCT+5-FU/MMC) with available paraffin-embedded tumor tissue specimens were evaluated regarding local control (LC) and overall survival (OS) at 5 years. In addition to HPV DNA/p16 status, the influence of age, gender, previous surgery, initial recurrence, T stage, N status, and tumor localization was analyzed. 63 patients were HPV+/p16+, 9 were HPV+/p16−, 11 were HPV−/p16+, and 23 were HPV−/p16−. In univariate analysis, LC was significantly better in patients with T1/2 stage, female gender, and HPV/p16 status. HPV+/p16+ was associated with significantly better LC (88.1%; 95% confidence interval [CI]: 78.89-97.31) compared with HPV−/p16+ (63.6%; 95% CI: 35.18-92.02; P=.021) and especially HPV−/p16− (55.8%; 95% CI: 33.46-78.14; P=.002) but not with HPV+/p16− (77.8%; 95% CI: 50.56-105.04; P=.270). OS was influenced by T stage and LC. HPV+/p16+ patients showed a trend toward better OS compared with HPV−/p16− patients (HPV+/p16+: 81.1%; 95% CI: 70.12-92.08 vs HPV−/p16−: 68.8%; 95%CI: 47.44-90.16; P=.138). On multivariate analysis, T3/4 stage and HPV/p16 status (HPV−/p16+, HPV−/p16− vs HPV+/p16+) predicted poorer LC (T3/4: 50.3% vs T1/2: 86.6%, hazard ratio [HR] 0.22; 95% CI: 0.09-0.53; P<.001; HPV+/p16+ vs HPV−/p16+: HR 4.73; 95% CI: 1.33-16.82; P=.016, and HPV+/p16+ vs HPV−/p16−: HR 6.40; 95% CI: 2.23-18.35; P<.001), whereas local relapse dramatically influenced OS. Our data suggest that HPV/p16 signature determines prognosis. HPV+/p16+ patients had the best prognosis, and HPV−/p16+ and HPV−/p16− patients showed the worst outcome and therefore require therapy optimization, particularly given that LC is the most important factor for OS.